METHODS OF DEVELOPING FUTURE PRIMARY SCHOOL TEACHERS’ DESIGN SKILLS BASED ON QUEST TECHNOLOGY (International Conference on Economics, Finance, Banking and Management, 2025)
This article explores the methods of developing design skills in future primary school teachers through the use of quest technology. The study emphasizes that the effective preparation of teachers for professional activity requires the integration of innovative pedagogical technologies that stimulate creativity, independence, and reflection. Quest technology, as a modern interactive teaching method, enables teacher trainees to design learning tasks, create motivating educational environments, and guide students through problem-solving processes. The paper discusses the pedagogical and psychological foundations of using quest technology in teacher education, highlights the stages of forming design competencies, and proposes effective methods for improving future teachers’ project-based skills.